THE EFFECT OF ACCOUNTABILITY AND TRANSPARENCY ON VILLAGE FUND MANAGEMENT (STUDY AT KANONANG ILLAE, MINAHASA) - Posumah Israel Moniung; Merinda H. C. Pandowo; Lawren J. Rumokoy (Universitas Sam Ratulangi, 2023)
This study aims to acquire empirical evidence regarding Accountability and Transparency on Village Fund Management. The Purpose of this research is to obtain empirical evidence regarding the effect of Accountability and Transparency on Village Fund Management. This research is quantitatively conducted where the respondents are 100 Villagers at Kanonang Village. The analytical method utilized in this research is multiple linear regression analysis. The analytical tool utilized SPSS. The results showed that Accountability have an effect on the Village Fund Management, Transparency have an effect on the Village Fund Management, and Accountability and Transparency have an effect on Village Fund Management. The Recommendation from this research is that the Kanonang Village Government needs to keep a track on the quality of human resources, effective information, and active community participation in the use of Village Fund Allocation for the Village Fund Management. Keywords: accountability, transparency, village fund management